If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 + -3(2x + 9) = 50 Reorder the terms: 5 + -3(9 + 2x) = 50 5 + (9 * -3 + 2x * -3) = 50 5 + (-27 + -6x) = 50 Combine like terms: 5 + -27 = -22 -22 + -6x = 50 Solving -22 + -6x = 50 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '22' to each side of the equation. -22 + 22 + -6x = 50 + 22 Combine like terms: -22 + 22 = 0 0 + -6x = 50 + 22 -6x = 50 + 22 Combine like terms: 50 + 22 = 72 -6x = 72 Divide each side by '-6'. x = -12 Simplifying x = -12
| 0.4(x+90)+0.2x=45 | | X^2+4x-169=0 | | -5x+6=9-6x | | 9+5a=-26 | | t-22=-23 | | 8n-8=5n+7 | | -16t^2+40t-65=0 | | -16t^2+40t+65=0 | | 1.5(4d-2)=d+5 | | 4x-2=-6+5x | | 2x^2-48x+48=0 | | n-3=17-4n | | 7x+10=5x+6 | | 2+2y=3 | | z-12/4=z/16 | | 2x-6(x+3)=2600 | | 3/4(z-5)=12z | | 2x-9=6x+7 | | 7x+6=5x+10 | | 6x+9x=-60 | | 4x-9x+1=21 | | x^3+7x^2+5x+35=0 | | 6x+3(x+1)=9x+6 | | (b+6)=7 | | 2+3d+d= | | -4(n-4)-23=7 | | 3b-24=11b | | 15=-d+8 | | 2(x-4)+5(x+3)=3x-12+2 | | -16t^2+40t-24=0 | | 10(x-1)-1x(x+4)=288 | | 6x-2=x-13 |